Comparison of pregnancy rates on day 3 and day 5 embryo transfer in In Vitro Fertilization (IVF) - Audia Mumtaz Rifasky; Puspa Wardhani; Ashon Sa’adi; Ninik Darsini; Hamdani Lunardhi; Zakiyatul Faizah (Majalah Obstetri dan Ginekologi, 2021)
Objectives: To identify the success rates of pregnancy on the third and fifth day embryo transfer at Graha Amerta Hospital, Surabaya, Indonesia.Materials and Methods: This study used comparative cross sectional design. Data were taken from medical record of IVF participants who met the inclusion and exclusion criteria at Graha Amerta Hospital for the period of January 2016 - December 2016.Results: Successful pregnancy rates were found in this research. The embryo transfer on the third day and the fifth day were 35% and 49.3% respectively. In other words, the rates of pregnancy success were not affected by embryo transfer on the third day and the fifth day in the medical record sample as it had p value of 0.090.Conclusion: Embryo transfer on the third and fifth days had the same rates of pregnancy success in IVF participants at Graha Amerta Hospital, Surabaya, Indonesia.